Regorafenib-related erythrocytosis in metastatic extra-gastrointestinal stromal tumor: a case report - Fassi, Elena; Amoroso, Vito; Cosentini, Deborah; Ferrari, Vittorio; Laganà, Marta; Berruti, Alfredo; di Mauro, Pierluigi (Frontiers in Oncology, 2024)
Introduction: Regorafenib is an oral multi-targeted tyrosine kinase inhibitor (TKI) indicated for the treatment of various tumor types, including metastatic gastrointestinal stromal tumors (GIST), as a third-line systemic therapy. Erythrocytosis, which is characterized by an increase in erythrocyte count, hemoglobin, and hematocrit levels, has been described as a side effect of some antiangiogenic TKIs but has never been associated with regorafenib administration. Case presentation: An extra-GIST was diagnosed in a 58-year-old woman after she underwent surgery to remove a pelvic mass. Three years later, systemic therapy with imatinib was started due to pelvic disease recurrence. However, after six months, due to disease progression, we prescribed sunitinib, which the patient received for four years. Regorafenib was initiated in June 2019, and after six months, we noted an increase in the erythrocytes' count and hemoglobin (Hb) levels. Given that the patient had clinical benefit and hematocrit was within normal range, we only monitored the blood cell count and continued to give regorafenib at the same dose. The drug was then stopped for over six weeks due to hospitalization for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and Hb levels returned to normal. Therefore, we decided to restart regorafenib at a lower dose. However, Hb levels rose again in conjunction with increased hematocrit, resulting in the need for multiple phlebotomies. We attempted to restart regorafenib every other day, but it was unsuccessful, so we stopped it permanently in May 2023, and all values returned to normal. Conclusion: Regorafenib may cause secondary erythrocytosis that could not be dose-related, as this case report suggests. Secondary erythrocytosis might be a marker of TKI efficacy, given the patient's prolonged clinical benefit during regorafenib treatment (48 months). In patients receiving regorafenib, monitoring blood count as well as any symptoms associated with erythrocytosis may be suggested.